Developing augmented reality in mathematics learning: The challenges and strategies - Guntur, Muhamad Ikhsan Sahal; Setyaningrum, Wahyu; Retnawati, Heri; Marsigit, Marsigit; Saragih, Novilda Angela; Noordin, Muhamad Kahir bin (Jurnal Riset Pendidikan Matematika, 2019)
One of the technologies developed massively in learning is Augmented Reality (AR) technology. This research will explain the challenges of teachers in developing AR-assisted learning media and strategies to anticipate the challenges that arise in developing AR-assisted learning media. This type of research is qualitative phenomenological research. The participants of this research were 75 Mathematics teachers who joined the developing AR-assisted learning media training. The teachers came from various regions in Indonesia. The mathematics teachers invited were 36 junior high school teachers and 29 senior high school teachers from public and private schools who were vulnerable at the age of 22-35 years and 27 teacher is male and the others are female. They have attended an AR-assisted media development training because have interested in AR and education. The data collection used is a questionnaire and an interview which is done to all participants and data analyzed using the Bogdan & Biklen model. The results of the research show that the challenges encountered by the teacher are meeting the minimum standards of hardware and software, limited references both sourced from humans, online media or print media. Efforts made by teachers to overcome existing problems such as gradually upgrading laptops, finding sources from foreign languages and trying to form joint learning communities.